An attribute-based perceptual mapping of different retail formats in India. (2017) - Yadav, Shalini; Garg, S.K.
The purpose of this study is to add to the existing knowledge-base by defining Indian customers' food retailer store choice preferences. This paper provides a general understanding of how consumers' associate selected retail grocery formats with the different attributes in the National Capital Region of Delhi. Discriminant analysis was conducted to examine the data to draw perceptual map for selected retail format along with different attributes. The results indicate that the hypermarket and supermarket do not differ significantly with regard to given attributes in the mind of the consumer. However, these retailers vary considerably on the basis of promotional campaigns, offers and advertisement. Moreover, we see a slow drift of the Indian consumer from traditional kirana format towards modern formats. The overall objective of this study is to suggest an inclusive assessment of the positioning of various retail attributes compared with retail formats as perceived by the consumer.